Comparative Nutritive Value of Meat in Commercial Native Chicken, Backyard Native Chicken, Commercial Broiler and Spent Layer Chicken: 10.5958/2581-6616.2020.00002.X - kumar, R. Sathish; Kulkarni, V. V.; Vasan , P. (Journal of Meat Science, 2021)
A study was planned on the nutritive value of meat in commercial native chicken (CNC), backyard native chicken (BNC), commercial broiler (CB) and spent layer chicken (SLC). An experiment was conducted on 12 birds of either sex in each class. Birds were slaughtered by Jatka method and nutritional composition and protein quality of each group were studied for breast and leg meat separately. Pro tein quality (biological value, true digestibility and net protein utility) of meat was studied by precision feeding trial in adult cockerels. Cholesterol content was significantly lower in CB and CNC. The true digestibility, biological value and net protein utility in SLC were significantly lower than other categories. Biological value and net protein utility was significantly higher (P<0.01) in CB than CNC, BNC and SLC. The lipid and cholesterol content were significantly higher (P<0.01) in thigh than breast meat. The study revealed that over all nutritive value of commercial broiler meat was better than commercial native chicken, backyard native chicken and spent layer chicken.